A Catholic Perspective on COVID-19 - Paris, John J. (Cambridge quarterly of healthcare ethics, 2024)
It took nearly two thousand years for society to recognize the Hippocratic insistence that "the doctor knows best"1 was an inadequate approach to medical decisionmaking. Today, patient-centered medicine has come to understand that the individual patient has a significant role in the decisionmaking process.2